Political scientists in NGOs, think tanks and consulting firms - Cabezas Rincón, Lina María (Política y Sociedad, 2024)
Political scientists have undergone major transformations in recent decades. In addition to gaining greater visibility in the public sphere, which allows them for social recognition, these professionals have expanded their field of action, from academia and public administration to NGOs, think tanks, and consultancy firms, among many others. These transformations are the result of processes of institutionalization and professionalization of the discipline, as well as several structural changes (technological transformation, diversification of the labor market, new complexity of politics, etc.).